Relevansi Pendidikan Karakter terhadap Prestasi Belajar Peserta Didik Kelas VI Pada Mata Pelajaran Pendidikan Kewarganegaraan di Madrasah Ibtidaiyah Haji Hasyim Babat Jerawat Pakal Surabaya - Febrilia Furiandini; Sutono Sutono; M. Luthfi Efendi (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
Character education is an educational effort in instilling human values and good habits to students. Learning achievement is the learning outcome obtained from the ability of students in a learning process with instructional objectives that bring changes in students as a result of the results of learning activities. Students are known at MI Haji Hasyim Surabaya have quite good character education. In line with good character education, student learning achievement is also quite good. The results of the study show that the character education of grade VI students at MI Haji Hasyim is generally in the very high category with an average value of 65.7%. Student character is reviewed from the discipline variable indicator in the strong correlation category with an average value of 0.768. Honesty is in the strong correlation category with an average value of 0.680. Responsibility is in the moderate correlation category with an average value of 0.529. Politeness is in the moderate correlation category with an average value of 0.570. Religion is in the strong correlation category with an average value of 0.797. The learning achievement of sixth-grade students in the subject of Character Education is in the very good category according to the achievement of the KKM value achieved by students of 77.1%. The relevance between Character Education and the learning achievement of sixth-grade students in the subject of Civics Education is in the medium correlation category with a correlation coefficient value of 0.442.